Uberização e precarização do trabalho face à pandemia do covid-19 - SILVA, Ana Beatriz Sá (2024)
This work aims to address the uberization of workers subject to the regime of subordination to applications and other digital platforms, especially accentuated in the post-COVID-19 pandemic period. It focuses on questioning the employment relationship existing between uberized workers and the mediator company, as well as the accentuation of precarious work in times of social crisis. We also seek a jurisprudential analysis of Brazilian law compared to decisions from international courts that also deal with the subject in an avant-garde manner by recognizing the existence of employment relationships and rights.